Targeting the Endothelin-1 pathway to reduce invasion and chemoresistance in gallbladder cancer cells - Francisco Rodas; Jetzabel A. Vidal-Vidal; Daniela Herrera; David A. Brown-Brown; Diego Vera; Joaquín Veliz; Pilar Püschel; José I. Erices; Verónica Sánchez Hinojosa; Julio C. Tapia; Eduardo Silva-Pavez; Claudia Quezada-Monrás; et al. (Cancer Cell International, 2023)
Abstract Background Gallbladder cancer (GBC) is a prevalent and deadly biliary tract carcinoma, often diagnosed at advanced stages with limited treatment options. The 5-year survival rate varies widely from 4 to 60%, mainly due to differences in disease stage detection. With only a small fraction of patients having resectable tumors and a high incidence of metastasis, advanced GBC stages are characterized by significant chemoresistance. Identification of new therapeutic targets is crucial, and recent studies have shown that the Endothelin-1 (ET-1) signaling pathway, involving ETAR and/or ETBR receptors (ETRs), plays a crucial role in promoting tumor aggressiveness in various cancer models. Blocking one or both receptors has been reported to reduce invasiveness and chemoresistance in cancers like ovarian, prostate, and colon. Furthermore, transcriptomic studies have associated ET-1 levels with late stages of GBC; however, it remains unclear whether its signaling or its inhibition has implications for its aggressiveness. Although the role of ET-1 signaling in gallbladder physiology is minimally understood, its significance in other tumor models leads us to hypothesize its involvement in GBC malignancy. Results In this study, we investigated the expression of ET-1 pathway proteins in three GBC cell lines and a primary GBC culture. Our findings demonstrated that both ETAR and ETBR receptors are expressed in GBC cells and tumor samples. Moreover, we successfully down-regulated ET-1 signaling using a non-selective ETR antagonist, Macitentan, which resulted in reduced migratory and invasive capacities of GBC cells. Additionally, Macitentan treatment chemosensitized the cells to Gemcitabine, a commonly used therapy for GBC. Conclusion For the first time, we reveal the role of the ET-1 pathway in GBC cells, providing insight into the potential therapeutic targeting of its receptors to mitigate invasion and chemoresistance in this cancer with limited treatment options. These findings pave the way for further exploration of Macitentan or other ETR antagonists as potential therapeutic strategies for GBC management. In summary, our study represents a groundbreaking contribution to the field by providing the first evidence of the ET 1 pathway's pivotal role in modulating the behavior and aggressiveness of GBC cells, shedding new light on potential therapeutic targets.